Total Synthesis of Auripyrone A Using a Tandem Non-Aldol Aldol-Paterson Aldol Process as a Key Step - Jung, Michael E. (2009)
A tandem non-aldol aldol-Paterson aldol generates the polypropionate 12 from the epoxy alcohol 8 and the ketone 9 in only two steps and 74% overall yield as a single diastereomer, due to double stereodifferentiation, where the stereoinduction from the enolate and the α-methyl substituent of the aldehyde are reinforcing. This compound was used for an efficient synthesis of the natural product auripyrone A, 1, in only 18 steps and 17% overall yield, using a highly regioselective hemiketalization of a keto diol and a late stage spiroketalization onto a stable hemiketal as the final key steps.